Basics of Islamic Education and Its Implementation in Indonesia - Rajaminsah, Rajaminsah; Badruzaman, Dudi; Ahmad, Irham Nur (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research article investigates the basics of Islamic education and its implementation in Indonesia to gain an in-depth understanding of the philosophical foundations and the dynamics of the implementation of Islamic education in the context of this country. This research article explores the foundational principles and examines the implementation of Islamic education in Indonesia. This type of research uses the Systematic Literature Review (SLR) method to learn the basics of Islamic education and its implementation in Indonesia. The data sources in the SLR method come from scientific literature in academic databases and other trusted sources of information. Data analysis in this research involves a systematic and comprehensive synthesis of relevant literature using a qualitative approach. The research's conclusion regarding the fundamentals and implementation of Islamic education in Indonesia underscores the pivotal role of a profound comprehension of religious, ethical, and moral values in crafting meaningful Islamic education. The implications of this research suggest the importance of ongoing adaptation and policy evolution in Islamic education in Indonesia to effectively address contemporary challenges and maintain its resonance with the diverse societal landscape.